Atlas of SPECT-CT - Fanti, Stefano (Springer, 2011)
The field of nuclear medicine has evolved rapidly in recent years, and one very important aspect of this progress has been the introduction of hybrid imaging systems. PET-CT has already gained widespread acceptance in many clinical settings, especially within oncology, and now SPECT-CT promises to emulate its success. Useful applications of this new approach have been identified not only in oncology but also in endocrinology, cardiology, internal medicine, and other specialties. This atlas, which includes hundreds of high-quality images, is a user-friendly guide to the optimal use and interpre.